2020
DOI: 10.1186/s12864-020-07138-0
|View full text |Cite
|
Sign up to set email alerts
|

Global mRNA and microRNA expression dynamics in response to anthracnose infection in sorghum

Abstract: Background Anthracnose is a damaging disease of sorghum caused by the fungal pathogen Colletotrichum sublineolum. Genome-wide mRNA and microRNA (miRNA) profiles of resistant and susceptible sorghum genotypes were studied to understand components of immune responses, and fungal induced miRNA and target gene networks. Results A total of 18 mRNA and 12 miRNA libraries from resistant and susceptible sorghum lines were sequenced prior to and after inoculation with C. sublineolum. Significant differences in transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…RNA was extracted from the developing grain before and after the genotypes were challenged by a mixture of spore suspension of five Fusarium and an Alternaria species. The sampling time points 0, 24 and 48 h after inoculation were based on our previous study on grain [ 46 ] and leaf [ 47 ] that defense related genes are induced within 24 to 48 h after inoculation. RNA samples from two of the time points (0 and 24 h) were used for sequencing as preliminary studies indicated that defense genes were already induced at 24 h after infection while the 48 h samples were used for validation studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted from the developing grain before and after the genotypes were challenged by a mixture of spore suspension of five Fusarium and an Alternaria species. The sampling time points 0, 24 and 48 h after inoculation were based on our previous study on grain [ 46 ] and leaf [ 47 ] that defense related genes are induced within 24 to 48 h after inoculation. RNA samples from two of the time points (0 and 24 h) were used for sequencing as preliminary studies indicated that defense genes were already induced at 24 h after infection while the 48 h samples were used for validation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sorghum defensins have not been studied as they are mostly grain specific and pathogen inducible whereas most previous studies focus on foliar tissues. It is notable that defensins were not prominently described in recent RNA-seq experiments conducted in leaf tissues of sorghum consistent with their grain specific expression [ 47 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both genomic regions explained only a limited portion of the variance for anthracnose resistance, suggesting their effects are determined by the parallel additive effects of other, yet to be detected loci. A gene expression atlas derived from anthracnose-differential line SC283 identified genes encoding immune receptors, MAPKs, pentatricopeptide repeat proteins, and WRKY transcription factors as the most highly expressed genes in response to infection 35 . Increasing the mapping population size or fine mapping these loci are not affordable approaches to detect minor additive effect genes.…”
Section: Discussionmentioning
confidence: 99%
“…Basic blue proteins in plants are copper-containing plantacyanins that are regulated via conserved microRNA408 (miR408), which is present in sorghum ( Zhang et al, 2011 ). Although, miR408 was not identified among the upregulated miRNAs detected by RNAseq in anthracnose-resistant sorghum cultivar SC383 following inoculation with C. sublineolum ( Fu et al, 2020 ), a miR408 induced basic blue protein in wheat has been demonstrated to have a role in resistance to stripe rust ( Puccinia striiformis f. sp. tritici ; Feng et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have used RNASeq to investigate differences in gene expression in early defense responses of two sorghum cultivars that differ significantly in anthracnose sensitivity to try to pinpoint genes and pathways that may contribute to that difference, and to compare results with another very recent publication that did similar experiments but with emphasis on microRNAs with a different pair of anthracnose resistant and susceptible cultivars ( Fu et al, 2020 ). Here, a mix of two C. sublineola isolates from Johnsongrass that had previously been shown lead to different visible responses on QL3 and Theis were used to examine gene expression changes in the two cultivars 24 h post-inoculation.…”
Section: Introductionmentioning
confidence: 99%